Big data analytics for mining geochemistry of gold mineralization: The Gandy gold deposit, the Toroud-Chah Shirin (TCS) belt, north Iran; Ore Geology Reviews; Vol. 161 - Abedini M. Mahnaz; Ziaii M. Mansour; Timkin T. V. Timothy Vasilyevich; Pour A. B. Amin Beiranvand (2023, 2023)
Title screen